Perbaikan Sifat Kimia Tanah dengan Penanaman Asystasia gangetica (L.) T. Anderson sebagai Cover Crop - Yenni Asbur (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
This decrease in land productivity is closely related to the reduced organic matter content in the soil, so efforts are needed to overcome it by utilizing asystasia gangetica weeds as a cover crop. The purpose of this study was to determine the benefits of A. gangetica as a cover crop in improving soil chemical properties under shaded and unshaded conditions. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Islamic University of North Sumatra (UISU), Johor Building, Medan. The research method used was a split plot design in a factorial randomized block design. The first factor as the main plot is Shade (N) and the second factor as the subplot is Cover crop (C) with three replications. The results of this study showed that A. gangetica grown as a cover crop was able to improve soil chemical properties by increasing the organic C, total N, and available K content of the soil after treatment. Likewise, the combination of both shaded and unshaded treatments with cover crop A. gangetica (N1C1 and N0C1) was able to improve soil chemical properties by increasing the C-organic, total N, and available K-content of the soil after treatment.